Análise de fósforo no recurso hídrico da microbacia hidrográfica da fazenda Glória, Taquaritinga, SP - Rodrigues, Flávia Mazzer [UNESP]; Pissarra, Teresa Cristina Tarlé [UNESP]; Campos, Sergio [UNESP] (My University, 2011)
The analysis of the way in hydrographic basins requires knowledge of the processes and characteristics of variable in different geographic scales. Leaving of the principle that the hydrographic basins can be hierarchy, those territorial units of ideal work for the analysis of the hydrological conditions are considered. This work had for objective to carry through a comparison of the conditions of waters resources in four hydrographic basins, with different use and occupation. Five points of sampling throughout the net of draining in the hydrographic basins of 1ª had been established magnitude order. Comparatively, in the hydrographic basins M2 and M3 bigger variability of the evaluated parameters occurred. The characterization of the hydrological conditions of the hydrographic basins indicated that the agricultural activities, including practical the cultural ones in the productive system had affected the quality of the waters resources.

A análise do meio em bacias hidrográficas requer um conhecimento dos processos e características de variáveis em diferentes escalas geográficas. Partindo do princípio que as microbacias podem ser hierarquizadas, elas são consideradas unidades territoriais de trabalho ideal para a análise das condições hidrológicas. Este trabalho teve por objetivo realizar uma comparação do parâmetro fósforo nas condições do recurso hídrico em quatro microbacias, com diferentes uso e ocupação do solo. Foram estabelecidos cinco pontos de amostragem ao longo da rede de drenagem nas microbacias de 1ª ordem de magnitude e um ponto na foz. As coletas de água ocorreram em intervalos mensais. Comparativamente, nas microbacias M2 e M3 ocorreu maior variabilidade dos parâmetros avaliados. A caracterização das condições hidrológicas das microbacias hidrografias indicou que as atividades agrícolas, incluindo as práticas culturais de atividades antrópicas interferem no recurso hídrico.
Analysis of phosphorus in the watershed of fazenda da Glória, Taquaritinga, SP
Keywords: Water resource; Environment; Environment monitoring; Recurso hídrico; Ambiente; Monitoramento ambiental